Using videoconferencing in a school-scientist partnership: students’ perceptions and scientists’ challenges - Garry Falloon (Association for Learning Technology, 2012)
This research studied a series of videoconference teaching workshops and virtual labs, which formed a component of a school-scientist partnership involving a New Zealand science research institute and year 13 students at a Wellington high school. It explored students’ perceptions of the effectiveness of the videoconferences as an interactive medium for developing content knowledge, identified factors influencing their level of interaction during the conferences, and exposed issues when using videoconferences for highly specialised activities. The research followed an interpretive methodology using a case study approach, and employed mixed method qualitative/quantitative data gathering procedures. Results suggest that while videoconferencing was effective it was also expensive and time-consuming, and that scientists’ efforts to engage students more interactively through movement towards more constructive practice, were largely ineffective. This article provides direction for teachers considering exploring the potential of interactive videoconferencing with students.